Au nom du père Sociologie des mobilisations de pères séparés - Fillod-Chabaud, Aurélie (Gouvernement en question(s), 2022)
"Parental equality", "sexist justice!". Regularly, men perch on top of monuments to hold up, for a few hours, signs displaying these slogans. These mobilizations, which can be seen all over the world, are protesting against a family justice system that would be unfavorable to men because it would massively organize the residence of children with their mothers, after the parents' separation. How can these mobilizations shed light on contemporary issues of family transformation and, more specifically, on the judicial regulation of post-marital parenthood? In the light of a field study among groups of separated fathers, Aurélie Fillod-Chabaud shows how much these mobilizations can be part of a reactionary and antifeminist movement, criticizing in essence the "feminization" of society and of the major State bodies. This book, based on a doctoral thesis in sociology, offers an analysis of the mobilisations of separated fathers from a comparative perspective (France-Quebec) for an academic, associative, and activist readership.